Sugar-sweetened beverage intake and cardiovascular risk factor profile in youth with type 1 diabetes: Application of measurement error methodology in the SEARCH Nutrition Ancillary Study - Liese, Angela D. (Br J Nutr, 2015)
OBJECTIVE: The SEARCH Nutrition Ancillary Study aims to investigate the role of dietary intake on the development of long-term complications of type 1diabetes in youth and capitalize on measurement error (ME) adjustment methodology. RESEARCH DESIGN AND METHODS: Using the National Cancer Institute (NCI) method for episodically-consumed foods, we evaluated the relationship of sugar-sweetened beverage (SSB) intake and cardiovascular risk factor profile, applying ME adjustment. The calibration sample included 166 youth with two FFQs and three 24-hour dietary recalls within one month. The full sample included 2,286 youth with type 1 diabetes. RESULTS: SSB intake was significantly associated with higher triglycerides, total and LDL-cholesterol, adjusted for energy, age, diabetes duration, race/ethnicity, gender, education. The estimated effect size was larger (model coefficients increased approximately threefold) after application of the NCI method than without ME adjustment. Compared to individuals consuming one serving of SSB every two weeks, those who consumed one serving every two days had 3.7 mg/dL higher triglycerides, 4.0 mg/dL higher total cholesterol and LDL cholesterol, adjusted for ME and covariates. SSB intake was not associated with measures of adiposity and blood pressure. CONCLUSIONS: Our findings suggest that SSB intake is significantly related to increased lipid levels in youth with type 1diabetes and that estimates of the effect size of SSB on lipid levels are severely attenuated in the presence of measurement error. Future studies in youth with diabetes should consider a design that will allow for the adjustment for measurement error when studying the influence of diet on health status.